Laminate

JP2026169309APending Publication Date: 2026-10-16SEKISUI CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026182471
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、ポリウレタン発泡体と被膜層とを備える積層体において、従来よりも最高発熱速度及び総発熱量が低く、難燃性の向上した積層体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169309000001
    Figure 2026169309000001
  • Figure 2026169309000002
    Figure 2026169309000002
Patent Text Reader

Abstract

To provide a laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam, wherein the laminate has improved flame retardancy compared to conventional laminates. [Solution] A laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam, wherein the polyurethane foam contains a solid phosphorus-based flame retardant and the coating layer contains limestone and metal hydroxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a laminate comprising a polyurethane foam and a coating layer. [Background technology]

[0002] Polyurethane foam is used in practical applications for insulation and condensation prevention in various structures such as ceilings, roofs, and walls of buildings, including apartment buildings, detached houses, and commercial buildings, due to its excellent thermal insulation properties. Polyurethane foam is formed, for example, by spraying a urethane resin composition containing a polyol composition and polyisocyanate onto the surface of each structure, followed by foaming and curing.

[0003] While commonly used polyurethane foams offer excellent heat insulation, they tend to be susceptible to heat, creating a demand for polyurethane foams with superior heat resistance. Patent Document 1 discloses an invention relating to a method for forming a composite heat insulating layer, characterized by forming an inorganic foam composition layer on the surface of a synthetic resin foam such as polyurethane foam. This layer consists of an inorganic foam composition obtained by adding aluminum powder to a slurry material mainly composed of calcareous raw materials such as cement. It is also stated that this method improves heat resistance. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Unexamined Patent Publication No. 61-72544 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] As mentioned above, it is generally known that a coating layer made of cement material or the like can be formed on the surface of polyurethane foam, which provides a certain degree of flame retardancy, such as preventing the surface from scorching. However, from the perspective of preventing ignition of polyurethane foam, higher flame retardancy is required. Specifically, the challenge is to reduce the maximum heat release rate and total heat release, as evaluated by the cone calorimeter test, compared to conventional methods. Therefore, the present invention aims to provide a laminate comprising a polyurethane foam and a coating layer that has a lower maximum heat generation rate and total heat generation amount than conventional laminates, and improved flame retardancy. [Means for solving the problem]

[0006] As a result of diligent research, the inventors have found that the above problems can be solved by a laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam, wherein the polyurethane foam contains a solid phosphorus-based flame retardant and the coating layer contains limestone and metal hydroxide, and have completed the present invention. That is, the present invention provides the following [1] to

[10] .

[0007] [1] A laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam, wherein the polyurethane foam contains a solid phosphorus-based flame retardant and the coating layer contains limestone and metal hydroxide. [2] The laminate according to [1] above, wherein the coating layer is formed of a coating material containing limestone, metal hydroxide, and water. [3] The laminate according to [1] or [2] above, wherein the metal hydroxide is at least one selected from the group consisting of magnesium hydroxide and aluminum hydroxide. [4] The laminate according to [2] or [3] above, wherein the metal hydroxide content in the coating material is 3 to 80% by mass on a basis of total solids. [5] The polyurethane foam is formed from a urethane resin composition containing a polyol, a polyisocyanate, a catalyst, a blowing agent, and a solid phosphorus-based flame retardant, and is a laminate according to any one of [1] to [4] above. [6] The laminate according to [5] above, wherein the catalyst comprises a trimerizing catalyst. [7] The laminate according to the above [6], wherein the trimerization catalyst comprises a quaternary ammonium salt. [8] The laminate according to any one of the above [5] to [7], wherein the catalyst comprises at least one metal catalyst selected from the group consisting of bismuth and tin. [9] The laminate according to any one of the above [5] to [8], wherein the catalyst comprises an imidazole derivative.

[10] The laminate according to any one of the above [5] to [9], wherein the urethane resin composition is for spraying. [Effects of the Invention]

[0008] According to the present invention, in a laminate comprising a polyurethane foam and a coating layer, it is possible to provide a laminate having a lower maximum heat release rate and lower total heat release than conventional ones, and improved flame retardancy. [Modes for Carrying Out the Invention]

[0009] The present invention is a laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam, wherein the polyurethane foam contains a solid phosphorus-based flame retardant, and the coating layer is a laminate containing limestone and a metal hydroxide.

[0010] In the laminate of the present invention, a coating layer is laminated on the surface of a polyurethane foam. The coating layer is preferably laminated on one surface of the polyurethane foam. In general, polyurethane foams are vulnerable to heat, but in the laminate of the present invention, the polyurethane foam contains a solid phosphorus-based flame retardant, and the coating layer contains a metal hydroxide, so the maximum heat release rate and total heat release are reduced, making it easier to prevent ignition.

[0011] [Polyurethane Foam] The polyurethane foam in the present invention is formed from a urethane resin composition containing a polyol, a polyisocyanate, a catalyst, a blowing agent, and a solid phosphorus-based flame retardant. The urethane resin composition is preferably for spraying. That is, the urethane resin composition is used by being sprayed onto any structure, and the polyurethane foam is formed on the structure. Although details will be described later, the spraying can be performed using a spraying apparatus or the like.

[0012] <Polyol> The urethane resin composition in the present invention contains a polyol. Examples of the polyol include polylactone polyols, polycarbonate polyols, polyester polyols, polymer polyols, and polyether polyols.

[0013] Examples of the polylactone polyol include polypropiolactone glycol, polycaprolactone glycol, and polyvalerolactone glycol. Examples of the polycarbonate polyol include polyols obtained by a dealcoholization reaction between a hydroxyl group-containing compound such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, and nonanediol, and ethylene carbonate, propylene carbonate, or the like.

[0014] Examples of the polyester polyol include polymers obtained by dehydration condensation of a polybasic acid and a polyhydric alcohol, and condensates of a hydroxycarboxylic acid and the aforementioned polyhydric alcohol or the like. Examples of the polybasic acid include adipic acid, azelaic acid, sebacic acid, isophthalic acid (m-phthalic acid), terephthalic acid (p-phthalic acid), o-phthalic acid (phthalic acid), naphthalenedicarboxylic acid, and succinic acid. Examples of the polyhydric alcohol include bisphenol A, ethylene glycol, 1,2-propylene glycol, 1,4-butanediol, diethylene glycol, 1,6-hexane glycol, and neopentyl glycol. Examples of hydroxycarboxylic acids include castor oil and reaction products of castor oil and ethylene glycol.

[0015] Examples of polymer polyols include polymers obtained by graft polymerization of ethylenically unsaturated compounds such as acrylonitrile, styrene, methyl acrylate, and methacrylate onto aromatic polyols, alicyclic polyols, aliphatic polyols, and polyester polyols, as well as polybutadiene polyols, or hydrogenated versions thereof.

[0016] Examples of polyether polyols include polymers obtained by ring-opening polymerization of at least one C2-C6 alkylene oxide, specifically ethylene oxide, propylene oxide, or tetrahydrofuran, in the presence of at least one low molecular weight active hydrogen compound having two or more active hydrogen atoms, such as a polyhydric alcohol. Examples of alkylene oxides include at least one of ethylene oxide and propylene oxide. Examples of low molecular weight active hydrogen compounds having two or more active hydrogen atoms include bisphenol A, ethylene glycol, propylene glycol, butylene glycol, diols such as 1,6-hexanediol, triols such as glycerin and trimethylolpropane, tetrahydric to octahydric alcohols such as pentaerythritol, sorbitol, mannitol, sorbitan, diglycerin, dipentaerythritol, sucrose, glucose, mannose, fructose, methyl glucoside and its derivatives, phloroglucinol, and cresol. Examples include polyols such as pyrogallol, catechol, hydroquinone, bisphenol A, bisphenol F, bisphenol S, 1,3,6,8-tetrahydroxynaphthalene, and 1,4,5,8-tetrahydroxyanthracene; castor oil polyols; (co)polymers of hydroxyalkyl (meth)acrylates; polyfunctional polyols (e.g., 2 to 100 functional groups) such as polyvinyl alcohol; condensates of phenol and formaldehyde (novolac); amines such as ethylenediamine and butylenediamine. As the polyether polyol, a Mannich-type polyether polyol may be used. A Mannich-type polyether polyol is obtained using the Mannich reaction and is a Mannich condensate having two or more hydroxyl groups in the molecule, or a polyether polyol obtained by adding an alkylene oxide to such a Mannich condensate.

[0017] Polyols used in the present invention are preferably polyester polyols and polyether polyols. Polyols having two hydroxyl groups are also preferred. Among these, aromatic polyester polyols, which are polyester polyols having an aromatic ring, are preferred from the viewpoint of improving the flame retardancy of the polyurethane foam. The aromatic polyester polyol is preferably a condensate of an aromatic dicarboxylic acid such as o-phthalic acid (phthalic acid), m-phthalic acid (isophthalic acid), p-phthalic acid (terephthalic acid), or naphthalenedicarboxylic acid with a glycol. In particular, from the viewpoint of improving the flame retardancy of the polyurethane foam, especially its ability to prevent flame spreading, the aromatic polyester polyol is more preferably a phthalic acid-based polyester polyol, which is a condensate of phthalic acid and glycol, and even more preferably at least one selected from p-phthalic acid-based polyester polyol, which is a condensate of p-phthalic acid and glycol, and o-phthalic acid-based polyester polyol, which is a condensate of o-phthalic acid and glycol.

[0018] When the polyol contains an aromatic polyester polyol, the amount is not particularly limited, but is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 80 parts by mass or more, and even more preferably 100 parts by mass, per 100 parts by mass of the polyol.

[0019] The weighted average hydroxyl value of the polyol is preferably 20 to 350 mg KOH / g, more preferably 50 to 300 mg KOH / g, and even more preferably 100 to 280 mg KOH / g. When the hydroxyl value of the polyol is below the upper limit, the viscosity of the polyol composition tends to decrease, which is preferable from the viewpoint of handling and other factors. On the other hand, when the hydroxyl value of the polyol is above the lower limit, the crosslinking density of the polyurethane foam increases, resulting in higher strength and better workability during spraying. The hydroxyl value of polyols can be measured according to JIS K 1557-1:2007.

[0020] Here, the weighted average hydroxyl value of a polyol is determined by the sum of the products of the hydroxyl values ​​of the individual polyols constituting the polyol and the weight fraction of each individual polyol in the polyol. For example, when using two types of polyols, (d1) and (d2), if the hydroxyl value of polyol (d1) is X1 and the amount added is m1, and the hydroxyl value of polyol (d2) is X2 and the amount added is m2, the weighted average hydroxyl value is expressed by the following formula. Note that the amounts m1 and m2 are parts by mass in 100 parts by mass of polyol. Weighted average hydroxyl value (mgKOH / g)=X1×(m1 / (m1+m2))+X2×(m2 / (m1+m2))

[0021] <Solid phosphorus-based flame retardant> The urethane resin composition in the present invention contains a solid phosphorus-based flame retardant. A laminate comprising a polyurethane foam formed from a urethane resin composition containing a solid phosphorus-based flame retardant is preferable because it has a lower maximum heat generation rate and a lower total heat generation amount. Here, "solid" means being in a solid state at room temperature (25°C) and normal pressure (1 atmosphere).

[0022] Examples of solid phosphorus-based flame retardants include red phosphorus-based flame retardants, phosphate-containing flame retardants, and phosphinic acid-based flame retardants. Among these, solid phosphorus-based flame retardants preferably contain red phosphorus-based flame retardants. Solid phosphorus-based flame retardants may be used individually or in combination of two or more types.

[0023] (Red phosphorus-based flame retardant) Red phosphorus-based flame retardants may be red phosphorus alone, red phosphorus coated with a resin, metal hydroxide, metal oxide, etc., or a mixture of red phosphorus and a resin, metal hydroxide, metal oxide, etc. The resin used to coat or mix with red phosphorus is not particularly limited, but examples include thermosetting resins such as phenolic resins, epoxy resins, unsaturated polyester resins, melamine resins, urea resins, aniline resins, and silicone resins. From the viewpoint of flame retardancy, metal hydroxides are preferred as the compound to be coated or mixed. The metal hydroxide should be appropriately selected and used from those described in the section on metal hydroxide-based flame retardants.

[0024] (Phosphate-containing flame retardant) Examples of phosphate-containing flame retardants include phosphates comprising a salt of phosphoric acid with at least one metal or compound selected from metals of groups IA to IVB of the periodic table, ammonia, aliphatic amines, and aromatic amines. While there are no specific limitations on phosphates, various types of phosphates can be mentioned, such as monophosphates, pyrophosphates, and polyphosphates. Examples of metals from groups IA to IVB of the periodic table include lithium, sodium, calcium, barium, iron(II), iron(III), and aluminum. Examples of aliphatic amines include methylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, and piperazine. Examples of aromatic amines include pyridine, triazine, and melamine. Furthermore, the above-mentioned phosphate-containing flame retardants may be subjected to known water-resistance-improving treatments, such as silane coupling agent treatment or coating with melamine resin.

[0025] Specific examples of phosphate-containing flame retardants include monophosphates, pyrophosphates, and polyphosphates. The monophosphates are not particularly limited, but examples include ammonium salts such as ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; lithium salts such as monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite, dilithium phosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, tribarium phosphate, and barium hypophosphite; magnesium salts such as magnesium monohydrogen phosphate, magnesium hydrogen phosphate, trimagnesium phosphate, and magnesium hypophosphite; calcium salts such as calcium dihydrogen phosphate, calcium hydrogen phosphate, tricalcium phosphate, and calcium hypophosphite; and zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite.

[0026] The polyphosphate is not particularly limited, but examples include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium polyphosphate amide, and aluminum polyphosphate. Among these, the use of polyphosphate is more preferable. A single phosphate-containing flame retardant may be used, or two or more types may be used together.

[0027] (Phosphinic acid-based flame retardant) Examples of phosphinic acid-based flame retardants include phosphinic acid, dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid.

[0028] The content of the solid phosphorus-based flame retardant in the urethane resin composition is preferably 5 to 150 parts by mass, more preferably 10 to 120 parts by mass, and even more preferably 15 to 100 parts by mass, per 100 parts by mass of polyol. When the content of the solid phosphorus-based flame retardant is above the lower limit, good flame retardancy can be imparted to the polyurethane foam, and the total heat generation and maximum heat generation rate of the laminate can be reduced. Furthermore, when the content of the solid phosphorus-based flame retardant is below the upper limit, the urethane resin composition can be sprayed over a wide area, and the adhesion of the formed polyurethane foam to the sprayed surface is improved.

[0029] <Solid flame retardants other than solid phosphorus-based flame retardants> The urethane resin composition in the present invention may contain solid flame retardants other than the solid phosphorus-based flame retardants described above. Examples of solid flame retardants other than solid phosphorus-based flame retardants include boron-based flame retardants, bromine-containing flame retardants, antimony-containing flame retardants, and metal hydroxide-based flame retardants. Furthermore, the term "solid flame retardant" is sometimes used to refer to both "solid phosphorus-based flame retardants" and "solid flame retardants other than solid phosphorus-based flame retardants."

[0030] (Boron-based flame retardant) Examples of boron-based flame retardants include alkali metal borates such as lithium borate, sodium borate, potassium borate, and cesium borate; alkaline earth metal borates such as magnesium borate, calcium borate, and barium borate; zirconium borate, zinc borate, aluminum borate, and ammonium borate. Among these, zinc borate is preferred.

[0031] (Bromine-based flame retardant) Brominated flame retardants are not particularly limited as long as they are compounds that contain bromine in their molecular structure, but examples include aromatic brominated compounds. Specific examples of the aromatic brominated compounds include, for example, monomer-based organic bromine compounds such as hexabromobenzene, pentabromotoluene, hexabromobiphenyl, decabromobiphenyl, hexabromocyclodecane, decabromodiphenyl ether, octabromodiphenyl ether, hexabromodiphenyl ether, bis(pentabromphenoxy)ethane, ethylenebis(pentabromophenyl), ethylenebis(tetrabromophthalimide), and tetrabromobisphenol A, as well as polycarbonate oligomers produced using brominated bisphenol A as a raw material, and the polycarbonate oligomer and bisphenol A. Examples include brominated polycarbonates such as copolymers of the following, diexo compounds produced by the reaction of brominated bisphenol A and epichlorohydrin, monoepoxy compounds obtained by the reaction of brominated phenols and epichlorohydrin, halogenated brominated compound polymers such as poly(brominated benzyl acrylate), brominated polyphenylene ether, brominated bisphenol A, cyanur chloride and brominated phenol condensates, brominated polystyrene such as brominated (polystyrene), poly(brominated styrene), and crosslinked brominated polystyrene, and crosslinked or non-crosslinked brominated poly(α-methylstyrene). Among these, ethylenebis(pentabromophenyl), ethylenebis(tetrabromophthalimide), and hexabromobenzene are preferred.

[0032] (Antimony-containing flame retardant) Examples of antimony-containing flame retardants used in the present invention include antimony oxide, antimony salts, and pyroantimony salts. Examples of antimony oxides include antimony trioxide and antimony pentoxide. Examples of antimonate salts include sodium antimonate and potassium antimonate. Examples of pyroantimonate salts include sodium pyroantimonate and potassium pyroantimonate. The antimony-containing flame retardant is preferably antimony oxide. Antimony-containing flame retardants may be used individually or in combination of two or more types.

[0033] (Metal hydroxide-based flame retardant) Examples of metal hydroxide-based flame retardants include magnesium hydroxide, calcium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, and tin hydroxide. Metal hydroxide-based flame retardants may be used individually or in combination of two or more types.

[0034] The content of solid flame retardants other than solid phosphorus-based flame retardants is, for example, 70% by mass or less, preferably 60% by mass or less, and more preferably 50% by mass or less, based on the total amount of solid flame retardants.

[0035] (Fillers other than solid flame retardants) Furthermore, the urethane resin composition may contain fillers other than the solid flame retardants described above. Fillers other than solid flame retardants are solid at room temperature (25°C) and atmospheric pressure (1 atm) and exist as powders in the urethane resin composition. As fillers other than solid flame retardants, alumina, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, ferrites, basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, barium carbonate, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, imogolite, sericite, glass beads, silica balloon, aluminum nitride, boron nitride, silicon nitride, graphite, carbon balloon, charcoal powder, various metal powders, magnesium sulfate, lead zirconate titanate, molybdenum sulfide, silicon carbide, various magnetic powders, fly ash, etc. can be used as appropriate. Fillers other than solid flame retardants may be used individually or in combination of two or more types.

[0036] (Liquid flame retardant) The urethane resin composition of the present invention preferably contains a liquid flame retardant. A liquid flame retardant is one that becomes liquid at room temperature (25°C) and normal pressure (1 atm). The liquid flame retardant is not particularly limited, but a phosphate ester-based flame retardant is preferred.

[0037] As phosphate ester-based flame retardants, monophosphate esters, condensed phosphate esters, etc., can be used. A monophosphate ester is a phosphate ester that has one phosphorus atom in its molecule. Examples of monophosphate esters include trialkyl phosphates such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, and tri(2-ethylhexyl) phosphate; halogen-containing phosphate esters such as tris(β-chloropropyl) phosphate; trialkoxy phosphates such as tributoxyethyl phosphate; aromatic ring-containing phosphate esters such as tricresyl phosphate, trixylenyl phosphate, tris(isopropylphenyl) phosphate, cresyldiphenyl phosphate, and diphenyl(2-ethylhexyl) phosphate; and acidic phosphate esters such as monoisodecyl phosphate and diisodecyl phosphate.

[0038] Examples of condensed phosphate esters include aromatic condensed phosphate esters such as trialkyl polyphosphates, resorcinol polyphenyl phosphates, bisphenol A polycresyl phosphates, and bisphenol A polyphenyl phosphates. Examples of commercially available condensed phosphate esters include "CR-733S," "CR-741," and "CR747" from Daihachi Chemical Industry Co., Ltd., and "ADEKA Stab PFR" and "FP-600" from ADEKA Corporation.

[0039] The phosphate ester flame retardants may be used individually from the above-mentioned types, or two or more may be used in combination. Among these, monophosphate esters are preferred from the viewpoint of making it easier to adjust the viscosity of the urethane resin composition and from the viewpoint of improving the flame retardancy of the polyurethane foam, and halogen-containing phosphate esters such as tris(β-chloropropyl) phosphate are more preferred.

[0040] The content of the liquid flame retardant in the urethane resin composition is not particularly limited, but is preferably 15 to 100 parts by mass, more preferably 20 to 80 parts by mass, and even more preferably 25 to 70 parts by mass, per 100 parts by mass of polyol. When the liquid flame retardant content is above these lower limits, it becomes easier to impart flame retardancy to polyurethane foam without excessively increasing the viscosity of the urethane resin composition or excessively increasing the content of powders such as solid flame retardants. Conversely, when the liquid flame retardant content is below these upper limits, foaming is not inhibited, making it easier to manufacture polyurethane foam.

[0041] <Catalyst> The urethane resin composition of the present invention contains a catalyst. The catalyst may contain, for example, one or both of a urethane catalyst and a trimerizing catalyst, and it is preferable that it contains both.

[0042] (trimerization catalyst) A trimerization catalyst is a catalyst that reacts with the isocyanate groups contained in polyisocyanate to trimerize them and promote the formation of an isocyanurate ring. By including a trimerization catalyst, a polyurethane foam containing a polyisocyanurate structure can be formed, thereby improving fire resistance. In addition, it facilitates the completion of the reaction of the isocyanate groups, making it easier to obtain a polyurethane foam with good foamability.

[0043] Examples of trimerizing catalysts include metal catalysts and ammonium salts. Examples of metal catalysts used as trimerizing catalysts (trimerizing metal catalysts) include potassium organic acids, preferably potassium octoates such as potassium 2-ethylhexanoate, potassium acetate, potassium propionate, potassium butanoate, potassium benzoate, and other potassium carboxylates having 2 to 8 carbon atoms. As the ammonium salt, tertiary ammonium salts such as triethylammonium salt and triphenylammonium salt, and quaternary ammonium salts such as tetramethylammonium salt, tetraethylammonium salt, and tetraphenylammonium salt can be used, but among these, quaternary ammonium salts are preferred. The ammonium salt is, for example, an ammonium salt of a carboxylic acid. Examples of carboxylic acids in the ammonium salt include saturated fatty acids having 1 to 10 carbon atoms, preferably 2 to 8 carbon atoms. The hydrocarbon group of the saturated fatty acid may be linear or branched, but branching is preferred. Specific examples of carboxylic acids include 2-ethylhexanoic acid, 2,2-dimethylpropanoic acid, acetic acid, and formic acid, but among these, 2,2-dimethylpropanoic acid is preferred. The trimerization catalyst may be used alone or two or more may be used in combination. From the viewpoint of improving the adhesion between the polyurethane foam and the coating layer, the trimerizing catalyst preferably contains a quaternary ammonium salt and a metal catalyst (trimerizing metal catalyst).

[0044] The content of quaternary ammonium salt in the urethane resin composition is preferably 0.5 to 15 parts by mass, more preferably 1 to 12 parts by mass, and even more preferably 3 to 10 parts by mass, per 100 parts by mass of polyol. By setting the above content of quaternary ammonium salt to be above the lower limit, good adhesion between the formed polyurethane foam and the coating layer can be achieved. Furthermore, by setting the content of the trimerizing catalyst to be below the upper limit, the reaction rate can be appropriately controlled. The content of the metal catalyst (trimerized metal catalyst) in the urethane resin composition is not particularly limited, but is preferably 0.2 to 10 parts by mass, more preferably 0.3 to 8 parts by mass, and even more preferably 0.6 to 5 parts by mass per 100 parts by mass of polyol. Furthermore, the content of the trimerizing catalyst in the urethane resin composition is preferably 0.7 to 25 parts by mass, more preferably 1.5 to 20 parts by mass, and even more preferably 4 to 15 parts by mass, per 100 parts by mass of polyol.

[0045] (Urethane catalyst) The catalyst in the present invention preferably contains a urethane catalyst. The urethane catalyst preferably contains a nitrogen-containing heterocyclic compound. By including a nitrogen-containing heterocyclic compound as the urethane catalyst, the stability with respect to hydrofluoroolefins, described later, is improved, thereby preventing the decomposition of hydrofluoroolefins and resulting in good foaming properties. Furthermore, the reaction rate can be kept above a certain level, improving the workability when spraying the urethane resin composition. Among the nitrogen-containing heterocyclic compounds, the catalyst in the present invention more preferably contains an imidazole derivative. As described above, imidazole derivatives are less affected by hydrofluoroolefins and facilitate the reaction between polyols and polyisocyanates while increasing the stability of the polyol composition. Therefore, by containing imidazole derivatives, the reactivity between polyols and polyisocyanates in the urethane resin composition is enhanced, resulting in even better foaming properties. The imidazole derivative is preferably an imidazole in which the 1st and 2nd positions are independently substituted with alkyl groups having 8 or fewer carbon atoms, and the alkyl groups preferably have 6 or fewer carbon atoms, more preferably 4 or fewer carbon atoms. A suitable specific example of an imidazole derivative is represented by the following general formula (1).

[0046] [ka] (In general formula (1), R 1 and R 2 Each of these independently represents an alkyl group having 1 to 8 carbon atoms or an alkenyl group having 2 to 8 carbon atoms.

[0047] R in general formula (1) 1 and R 2 Each of these independently represents an alkyl group having 1 to 8 carbon atoms or an alkenyl group having 2 to 8 carbon atoms. The alkyl group and alkenyl group may each be linear or have a branched structure. Specific examples of the alkyl group include methyl group, ethyl group, propyl group, isopropyl group, butyl group, isobutyl group, sec-butyl group, pentyl group, neopentyl group, isopentyl group, sec-pentyl group, hexyl group, heptyl group, octyl group and the like. Specific examples of the alkenyl group include vinyl group, 1-propenyl group, allyl group, isopropenyl group, 1-butenyl group, 2-butenyl group, pentenyl group, hexenyl group, heptenyl group, octenyl group and the like. R 1 and R 2 the number of carbon atoms in the alkyl group or alkenyl group is not less than the aforementioned lower limit, the steric hindrance increases and the group becomes less susceptible to the influence of blowing agents such as hydrofluoroolefins, which is preferable. On the other hand, when the number of carbon atoms in the alkyl group of R 1 and R 2 is not more than the aforementioned upper limit, the steric hindrance does not become extremely large, so that the reaction between the polyol and the polyisocyanate can proceed rapidly, and the foamability also becomes favorable. From these viewpoints, R 1 and R 2 are each independently preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and even more preferably a methyl group.

[0048] Examples of the imidazole derivative represented by the general formula (1) include 1,2-dimethylimidazole, 1-ethyl-2-methylimidazole, 1-methyl-2-ethylimidazole, 1,2-diethylimidazole, 1-isobutyl-2-methylimidazole and the like. Among these, 1,2-dimethylimidazole and 1-isobutyl-2-methylimidazole are preferable from the viewpoints of improving the activity of the catalyst in the presence of hydrofluoroolefin and allowing the reaction to proceed rapidly. Further, 1,2-dimethylimidazole is even more preferable from the viewpoint of further enhancing stability.

[0049] The content of nitrogen-containing heterocyclic compounds in the urethane resin composition is preferably 0.1 to 20 parts by mass, more preferably 1 to 15 parts by mass, and even more preferably 2 to 10 parts by mass, per 100 parts by mass of polyol. When the content of nitrogen-containing heterocyclic compounds is above the lower limit, urethane bond formation occurs more easily, the reaction proceeds rapidly, and foaming properties are good. On the other hand, when the content of nitrogen-containing heterocyclic compounds is below the upper limit, the reaction rate is easier to control, which is preferable.

[0050] The urethane catalyst preferably contains a metal catalyst in addition to a nitrogen-containing heterocyclic compound. This metal catalyst is generally called a urethane-metal catalyst. In the present invention, the inclusion of the above-mentioned urethane-metal catalyst promotes the reaction between the polyol and the polyisocyanate, and in particular, the initial reaction rate can be increased. Furthermore, the inclusion of the urethane-metal catalyst makes it easier to maintain good foaming properties of the urethane resin composition. From the viewpoint of foaming properties, the catalyst preferably contains at least one metal catalyst (urethane-metal catalyst) selected from the group consisting of bismuth and tin, and more preferably contains bismuth. Bismuth has low reactivity to hydrofluoroolefins, which will be described later, and has high storage stability. It also makes it easier to achieve good initial activity without reducing the flame retardancy of the polyurethane foam.

[0051] The urethane metal catalyst described above is preferably a metal salt selected from bismuth and tin, and more preferably a bismuth salt. The metal salt is preferably an organic acid metal salt, and more preferably a metal salt of a carboxylic acid having 5 or more carbon atoms. Having 5 or more carbon atoms in the carboxylic acid provides good stability against blowing agents, especially hydrofluoroolefins. Furthermore, from the viewpoint of catalytic activity, the number of carbon atoms in the carboxylic acid is preferably 18 or less, and more preferably 12 or less. The carboxylic acid is preferably an aliphatic carboxylic acid, and more preferably a saturated aliphatic carboxylic acid. The carboxylic acid may be linear or have a branched structure, but it is preferable to have a branched structure. Specific examples of carboxylic acids include octyl acid, lauryl acid, versatic acid, pentanoic acid, and acetic acid, with octyl acid being preferred among these. In other words, the transition metal salt is preferably a metal salt of octyl acid. These carboxylic acids may be linear as described above, but they may also have a branched structure. An example of octyl acid having a branched structure is 2-ethylhexanoic acid. Preferred metal salts of carboxylic acids include bismuth salts and tin salts of carboxylic acids, with bismuth salts of octic acid being particularly preferred. Alternatively, the metal salt of the carboxylic acid may be an alkyl metal carboxylic acid salt. For example, the tin salt of the carboxylic acid may be a dialkyltin carboxylic acid salt, and preferably a dioctyltin carboxylic acid salt. Specific examples of metal salts of carboxylic acids include bismastrioctate, dioctyltin versatate, dibutyltin dilaurate, dioctyltin dilaurate, and tin dioctylate, with bismastrioctate and dioctyltin versatate being preferred, and bismastrioctate being more preferred.

[0052] The content of the above-mentioned urethane metal catalyst in the urethane resin composition is not particularly limited, but is preferably 0.05 to 8 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass per 100 parts by mass of polyol.

[0053] <Foaming agent> The urethane resin composition in the present invention contains a blowing agent. Specific examples of blowing agents include, for example, water, low-boiling hydrocarbons, chlorinated aliphatic hydrocarbon compounds, fluorine compounds, hydrochlorofluorocarbon compounds, hydrofluorocarbons, ether compounds, and hydrofluoroolefins. Furthermore, examples of blowing agents include organic physical blowing agents such as mixtures of these compounds, and inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas. Examples of the low-boiling hydrocarbons mentioned above include propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane. Examples of the above-mentioned chlorinated aliphatic hydrocarbon compounds include dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride. Examples of the fluorine compounds mentioned above include CHF3, CH2F2, and CH3F. Examples of the above-mentioned hydrochlorofluorocarbon compounds include trichloromonofluoromethane, trichlorotrifluoroethane, and dichloromonofluoroethane (e.g., HCFC141b (1,1-dichloro-1-fluoroethane), HCFC22 (chlorodifluoromethane), HCFC142b (1-chloro-1,1-difluoroethane)). Examples of the above-mentioned hydrofluorocarbons include HFC-245fa (1,1,1,3,3-pentafluoropropane) and HFC-365mfc (1,1,1,3,3-pentafluorobutane). Examples of the ether compounds mentioned above include diisopropyl ether. Examples of the above-mentioned hydrofluoroolefins include HFO-1233zd(E) (trans-1-chloro-3,3,3-trifluoropropene), HFO-1234yf (2,3,3,3-tetrafluoro-1-propene), HFO-1336mzz(Z) (cis-1,1,1,4,4,4-hexafluorobuta-2-ene), and HFO-1224yd(Z).

[0054] Among the above, hydrofluoroolefins and water are preferred as foaming agents, and it is preferable to use hydrofluoroolefins and water in combination. As the water used as a foaming agent, for example, ion-exchanged water, distilled water, etc. can be used as appropriate.

[0055] From the viewpoint of adjusting density and improving adhesion between the polyurethane foam and the coating layer, the foaming agent content is preferably 10 to 70 parts by mass, more preferably 15 to 65 parts by mass, and even more preferably 20 to 60 parts by mass, per 100 parts by mass of polyol.

[0056] When using hydrofluoroolefin as a foaming agent, the hydrofluoroolefin content is preferably 5 to 65 parts by mass, more preferably 10 to 60 parts by mass, and even more preferably 15 to 55 parts by mass, per 100 parts by mass of polyol, from the viewpoint of density adjustment and improving adhesion between the polyurethane foam and the coating layer. When water is used as a foaming agent, the water content is preferably 0.1 to 5 parts by mass, more preferably 0.1 to 2.5 parts by mass, and even more preferably 0.5 to 2 parts by mass, per 100 parts by mass of polyol, from the viewpoint of improving adhesion between the polyurethane foam and the coating layer.

[0057] <Foam stabilizer> The urethane resin composition of the present invention may contain a foam stabilizer. A compound having both a polar and a non-polar portion within its molecule and possessing a surfactant effect can be suitably used as the foam stabilizer. The foam stabilizer is not particularly limited, but examples include surfactants such as polyoxyalkylene foam stabilizers like polyoxyalkylene alkyl ethers and silicone foam stabilizers like organopolysiloxanes. As a silicone foam stabilizer, a graft copolymer of polyoxyalkylene glycol, which is a polymer of ethylene oxide or propylene oxide, and polydimethylsiloxane may also be used. Commercially available products can also be used, specifically foam stabilizers such as SH-193 (manufactured by Toray Dow Corning), B8467 (manufactured by Evonik), F501 (manufactured by Shin-Etsu Chemical Co., Ltd.), and SF-2937F (manufactured by Dow Toray). The foam stabilizer content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of polyol. When the foam stabilizer content is below these upper limits, the surface condition of the polyurethane foam improves, and the adhesion between the polyurethane foam and the coating layer is more easily improved. The foam stabilizer content is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, per 100 parts by mass of polyol. When the foam stabilizer content is above these lower limits, the stability of foaming tends to improve.

[0058] <Polyisocyanate> The urethane resin composition in the present invention contains polyisocyanate. As the polyisocyanate contained in the urethane resin composition, various polyisocyanate compounds such as aromatic, alicyclic, and aliphatic compounds having two or more isocyanate groups can be used. Preferably, liquid diphenylmethane diisocyanate (MDI) is used due to its ease of handling, rapid reaction, excellent physical properties of the resulting polyurethane foam, and low cost. Examples of liquid MDI include crude MDI (also called polymeric MDI). Specific commercially available liquid MDIs include "44V-10" and "44V-20" (manufactured by Sumika Covestro Urethane Co., Ltd.) and "Millionate MR-200" (Nippon Polyurethane Industry Co., Ltd.). Alternatively, uretonimine-containing MDI (for example, "Millionate MTL": manufactured by Nippon Polyurethane Industry Co., Ltd.) may also be used. Furthermore, a polyisocyanate compound may be treated in advance to increase its affinity with polyols by reacting some of the isocyanate active groups in the polyisocyanate compound with a hydroxyl group-containing compound. In addition to liquid MDI, other polyisocyanates may be used in combination, and any polyisocyanate known in the field of polyurethanes can be used without limitation.

[0059] The isocyanate index of the urethane resin composition of the present invention is preferably 150 or higher, more preferably 200 or higher, and even more preferably 250 or higher, from the viewpoint of properly forming polyurethane foam and imparting good flame retardancy. Furthermore, the isocyanate index of the urethane resin composition is preferably 800 or less, more preferably 600 or less, and even more preferably 500 or less. When the isocyanate index is below these upper limits, flame retardancy that is sufficiently commensurate with the manufacturing cost can be obtained. The isocyanate index (INDEX) is calculated using the following method.

[0060] INDEX = Equivalents of polyisocyanate ÷ (Equivalents of polyol + Equivalents of water) × 100 Here, Equivalent weight of polyisocyanate = Number of parts of polyisocyanate used × NCO content (%) × 100 / Molecular weight of NCO The equivalent weight of the polyol = OHV × the amount of polyol used ÷ the molecular weight of KOH, where OHV is the hydroxyl value of the polyol (mgKOH / g). Equivalent amount of water = Number of parts of water used × Number of OH groups in water / Molecular weight of water In the above formula, the unit of the number of parts used is weight (g), the molecular weight of the NCO group is 42, the NCO content is the proportion of NCO groups in the polyisocyanate compound expressed in mass%, and for the sake of unit conversion in the above formula, the molecular weight of KOH is assumed to be 56100, the molecular weight of water is assumed to be 18, and the number of OH groups in water is assumed to be 2.

[0061] The polyisocyanate content in the urethane resin composition can be adjusted as appropriate to fall within the range of the isocyanate index described above, but is, for example, 100 to 600 parts by mass, preferably 150 to 450 parts by mass, per 100 parts by mass of polyol.

[0062] (Other ingredients) The urethane resin composition in the present invention may, as necessary and without impairing the objectives of the present invention, contain one or more antioxidants such as phenolic, amine, and sulfur-based antioxidants, heat stabilizers, light stabilizers, metal damage inhibitors, antistatic agents, stabilizers, crosslinking agents, lubricants, softeners, pigments, dyes, etc.

[0063] There are no particular limitations on the method for producing the urethane resin composition of the present invention; for example, it can be produced by mixing each component. Although the urethane resin composition can be produced by mixing each component as described above, it is preferable to first prepare a polyol composition containing the polyol, catalyst, blowing agent, and solid phosphorus-based flame retardant, and then mix polyisocyanate into the polyol composition to prepare the urethane resin composition. The polyol composition may also contain solid flame retardants other than the solid phosphorus-based flame retardant, liquid flame retardants, etc.

[0064] The polyurethane foam in the present invention is formed from the above-described urethane resin composition, and more specifically, is obtained by foaming and curing the urethane resin composition.

[0065] (Foam density, thickness) The density of the polyurethane foam in this invention is not particularly limited, but is 30 kg / m³. 3 Preferably, the density is 30 kg / m³. 3 By doing so, shrinkage of the polyurethane foam is reduced, and delamination of the coating layer from the polyurethane foam constituting the laminate is suppressed. From this viewpoint, the density of the polyurethane foam is preferably 33 kg / m³. 3 The above is preferable, 35 kg / m 3 That's all. Furthermore, considering factors such as reducing the weight of the polyurethane foam and ease of application to the target surface, the density of the polyurethane foam is set at 200 kg / m³. 3 Preferably, it is 100 kg / m 3 The following is more preferable: The density of the polyurethane foam can be measured in accordance with JIS K7222.

[0066] The thickness of the polyurethane foam in the present invention is not particularly limited, but is, for example, 10 to 200 mm, and preferably 15 to 100 mm.

[0067] [Coating layer] The laminate of the present invention comprises a coating layer laminated on the surface of the polyurethane foam described above. The coating layer contains limestone and metal hydroxide, and can suppress the ignition of the polyurethane foam at high temperatures. The coating layer is formed from a coating material containing limestone, metal hydroxide, and water. The coating material used to form the coating layer will be described below.

[0068] (limestone) The coating material in this invention contains limestone. Preferably, the limestone is limestone included as a component of cement material. Therefore, it is preferable that the coating material contains a cement material containing limestone. This improves the mechanical strength and flame retardancy of the coating layer. Examples of cement materials include Portland cement, white cement, blast furnace cement, silica cement, and fly ash cement, with white cement being the preferred choice. The limestone content in the coating material is not particularly limited, but is, for example, 10 to 100% by mass, preferably 20 to 85% by mass, and more preferably 40 to 80% by mass, based on the total solid content. The limestone content in the coating material based on the total solid content is equivalent to the limestone content in the coating layer formed by the coating material.

[0069] (metal hydroxide) The coating material in this invention contains metal hydroxide. The inclusion of metal hydroxide improves the flame retardancy of the coating layer formed by the coating material. This is thought to be because the dehydration and endothermic properties of the metal hydroxide at high temperatures inhibit heat transfer. Therefore, the total heat generation and maximum heat generation rate of the laminate of the coating layer and polyurethane foam can be reduced. The type of metal hydroxide is not particularly limited, but examples include magnesium hydroxide, aluminum hydroxide, calcium hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, and tin hydroxide. Among these, from the viewpoint of improving flame retardancy, it is preferable that the metal hydroxide is at least one selected from the group consisting of magnesium hydroxide and aluminum hydroxide, and more preferably aluminum hydroxide.

[0070] The content of metal hydroxide in the coating material is not particularly limited, but is, for example, 3 to 80% by mass, preferably 5 to 60% by mass, and more preferably 10 to 45% by mass, based on the total solid content. The content of metal hydroxide in the coating material based on the total solid content is equivalent to the content of metal hydroxide in the coating layer formed by the coating material.

[0071] (water) The coating material contains water as a component other than the limestone and metal hydroxide mentioned above. The inclusion of water increases the fluidity of the coating material, making it easier to form a coating layer on polyurethane foam by application or other means. The water content in the coating material is not particularly limited, but is, for example, 50 to 500 parts by mass, preferably 80 to 300 parts by mass, and more preferably 100 to 200 parts by mass, per 100 parts by mass of total solids contained in the coating material.

[0072] (Other ingredients) The coating material may also contain other components besides the limestone, metal hydroxide, and water mentioned above. Other components include, for example, lightweight aggregates such as perlite, vermiculite, shirasu balloons, glass balloons, vermiculite, perlite, obsidian, volcanic rock, and natural pumice, as well as thickeners, surfactants, pigments, rust inhibitors, and dust inhibitors.

[0073] The coating layer can be formed by applying the above-mentioned coating material to the surface of the polyurethane foam by methods such as spraying or troweling, and then drying it. The thickness of the coating layer is, for example, 0.1 to 20 mm, preferably 0.5 to 15 mm, more preferably 1 to 10 mm, and even more preferably 2 to 8 mm, from the viewpoint of adequately protecting the polyurethane foam base from heat and from the viewpoint of reducing the weight of the laminate.

[0074] <Method for manufacturing laminates> The present invention preferably provides a method for producing a laminate that includes the steps of: spraying a urethane resin composition containing a polyol, a polyisocyanate, a catalyst, a blowing agent, and a solid phosphorus-based flame retardant onto the surface of a structure to form a polyurethane foam; and forming a coating layer on the polyurethane foam.

[0075] In the process of forming the polyurethane foam described above, a urethane resin composition containing a polyol, polyisocyanate, catalyst, blowing agent, and solid phosphorus-based flame retardant is sprayed onto the surface of a structure (substrate) to foam and cure the urethane resin composition and form a polyurethane foam. The structure described above is not particularly limited, but examples include buildings, furniture, automobiles, trains, ships, etc., but it is preferable to spray on buildings such as walls, ceilings, roofs, and floors. Spraying can be carried out using a spraying device (e.g., GRACO A-25) and a spray gun (e.g., Gasmar D-gun). Spraying can be carried out, for example, by adjusting the temperature of a polyol composition (preferably a polyol composition containing a polyol, catalyst, blowing agent, and solid phosphorus-based flame retardant) and polyisocyanate in a separate container within the spraying device, causing the two to collide and mix at the tip of the spray gun, and then atomizing the mixture with air pressure. The spraying device and spray gun are well-known and commercially available products can be used. Furthermore, the raw material temperature setting, pressure, etc., can be the same as the general spraying conditions for polyurethane foam.

[0076] In the process of forming a coating layer on the polyurethane foam described above, the coating material is applied to the polyurethane foam formed on the surface of the structure. Methods of application include, for example, spraying using a spraying device such as a mortar pump, or trowel application. After applying the coating material, the coating layer is formed by drying.

[0077] As described above, a laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam can be manufactured. The laminate of the present invention has a lower maximum heat generation rate and total heat generation amount than conventional laminates, and exhibits excellent flame retardancy. [Examples]

[0078] The present invention will be described in more detail by reference to examples, but the present invention is not limited in any way by these examples.

[0079] The details of each component used in each example and comparative example are as follows.

[0080] [Urethane resin composition] <Polyol> • p-phthalate-based polyester polyol (manufactured by Kawasaki Chemical Industries, Ltd., product name: Maximol RLK-087, hydroxyl value = 200 mg KOH / g)

[0081] <Catalyst> (1) Trimerization catalyst • Quaternary ammonium salt: tetramethylammonium 2,2-dimethylpropanoate (Evonik, product name: DABCO TMR7), concentration 45-55% by mass • Metal catalyst: Potassium 2-ethylhexanoate (Evonik, product name: DABCO K-15), concentration 70-80% by mass (2) Urethane catalyst • Bismastrioctate (manufactured by Nitto Kasei Co., Ltd., product name: Neostan U-600) concentration 55-58% by mass • 1,2-dimethylimidazole (manufactured by Tosoh Corporation, product name: TOYOCAT(registered trademark)-DM70) concentration 65-75% by mass

[0082] <Liquid Flame Retardant> • Phosphate ester-based flame retardant: Tris(β-chloropropyl) phosphate (manufactured by Daihachi Chemical Co., Ltd., product name: TMCPP)

[0083] <Solid phosphorus-based flame retardant> • Red phosphorus (manufactured by Phosphorus Chemical Industry Co., Ltd., product name: Nova Excel 140) • Polyphosphate: Ammonium polyphosphate (Clariant Corporation, product name: AP422) • Phosphate (Clariant, product name: OP1230)

[0084] <Solid flame retardants other than solid phosphorus-based flame retardants> • Zinc borate (Firebrake ZB, manufactured by Hayakawa Shoji Co., Ltd.)

[0085] <Foaming agent> • Water with deionized water • HFO-1233zd(E) <Hydrofluoroolefin> (Honeywell, product name: Solstice LBA)

[0086] <Polyisocyanate compounds> • 4,4'-Diphenylmethane diisocyanate (4,4'-MDI) (manufactured by Manka Chemical Japan Co., Ltd., product name: PM200)

[0087] [Coating material] <Limestone> Limestone was incorporated into the coating material by blending it with the following Dancoat SF. • "Dancoat SF" manufactured by Ohashi Chemical Industry Co., Ltd., contains white cement.

[0088] <Metal hydroxide> • Aluminum hydroxide: "B-325" manufactured by Almorix Corporation • Magnesium hydroxide: "Kyowa Suimag F" manufactured by Kyowa Chemical Industry Co., Ltd.

[0089] [Example 1] A polyurethane foam was obtained using a polyol composition prepared by mixing the polyol, flame retardant, catalyst, and blowing agent listed in Table 1, and the polyisocyanate listed in Table 1, under the following conditions. The composition of the urethane resin composition obtained by mixing the polyol composition and the polyisocyanate is as shown in Table 1. <Sample preparation conditions> • Spraying machine: Graco H-25 spraying device • Settings (Heater settings) Isocyanate heater: 38℃ Premix heater (for heating polyol compositions): 38℃ Hose heater (for pre-mixing heating of polyisocyanate and polyol compositions): 38°C • Base material: Gypsum board • Substrate temperature (temperature of the surface to be sprayed): 20℃±1℃

[0090] As described above, a sample was obtained in which polyurethane foam was formed on a gypsum board. This sample was cut out from the polyurethane foam side to include the gypsum board, with dimensions of 10 cm in length, 10 cm in width, and 3.5 cm in thickness. A portion of the cut-out sample was gypsum board, with 1.25 cm of the gypsum board and 2.25 cm of the polyurethane foam being the total thickness of 3.5 cm. The surface of the cut polyurethane foam sample was coated with a coating material having the composition described in Table 1, and dried at 25°C for one week. In this way, a sample for cone calorimeter testing was obtained, which included a laminate in which a coating layer was laminated on the surface of the polyurethane foam.

[0091] [Total heat output, maximum heat generation rate (CCM: Corn Calorimeter)] The cone calorimeter test samples obtained as described above were subjected to a test in accordance with ISO-5660, with a radiant thermal intensity of 50 kW / m². 2 Total heat output (MJ / m²) when heated for 10 minutes 2 The maximum heat generation rate (kW / m²) was measured when heated for 10 minutes under the same conditions. 2) was measured. (Total heat generation) 〇: Total heat output over 10 minutes is 8 MJ / m³ 2 below ×: Total heat output over 10 minutes is 8 MJ / m³ 2 bigger (Maximum heat generation rate) ◎: 20kW / m 2 less than ○: 20kW / m 2 More than 50kW / m 2 less than ×: 50kW / m 2 That's all.

[0092] [Examples 2-11, Comparative Examples 1-2] Except for changing the composition as shown in Table 1, a sample for the cone calorimeter test was prepared in the same manner as in Example 1, and the total calorific value and maximum heat generation rate were measured.

[0093] [Table 1]

[0094] Note that the mass parts of each catalyst represent the mass parts of the product.

[0095] The laminates of each embodiment that satisfy the requirements of the present invention exhibit low total heat generation and high maximum heat generation rate, indicating improved flame retardancy. In contrast, the laminate of Comparative Example 1, which does not contain metal hydroxide in the coating material, exhibits high total heat generation and high maximum heat generation rate. Even in Comparative Example 2, which had a thicker coating layer than Comparative Example 1, the total heat generation was still high. From this, it can be seen that the laminates of each comparative example that do not satisfy the requirements of the present invention are less flame-retardant than the laminates of the embodiments.

Claims

1. A laminate comprising a polyurethane foam and a coating layer laminated on the surface of the polyurethane foam, The polyurethane foam contains a solid phosphorus-based flame retardant. The aforementioned coating layer is a laminate containing limestone and metal hydroxide.

2. The laminate according to claim 1, wherein the coating layer is formed from a coating material containing limestone, metal hydroxide, and water.

3. The laminate according to claim 1 or 2, wherein the metal hydroxide is at least one selected from the group consisting of magnesium hydroxide and aluminum hydroxide.

4. The laminate according to claim 2, wherein the metal hydroxide content in the coating material is 3 to 80% by mass on a basis of total solid content.

5. The laminate according to claim 1, wherein the polyurethane foam is formed from a urethane resin composition containing a polyol, a polyisocyanate, a catalyst, a blowing agent, and a solid phosphorus-based flame retardant.

6. The laminate according to claim 5, wherein the catalyst includes a trimerizing catalyst.

7. The laminate according to claim 6, wherein the trimerizing catalyst contains a quaternary ammonium salt.

8. The laminate according to claim 5 or 6, wherein the catalyst comprises at least one metal catalyst selected from the group consisting of bismuth and tin.

9. The laminate according to claim 5 or 6, wherein the catalyst comprises an imidazole derivative.

10. The laminate according to claim 5 or 6, wherein the urethane resin composition is for spraying.

Citation Information

Patent Citations

  • Method of forming composite heat-insulating layer

    JP1986072544A